2023
DOI: 10.12659/msm.940041
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of the Neutrophil-to-Lymphocyte Ratio, Platelet-to-Lymphocyte Ratio, and Monocyte-to-Lymphocyte Ratio Esophageal Stricture After Endoscopic Submucosal Dissection of Early Esophageal Cancer

Abstract: Background Endoscopic submucosal dissection (ESD) has become a preferred treatment method for patients with early esophageal cancer (EEC), but it can easily be complicated by esophageal stricture. In this study, we aimed to analyze the predictive value of neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and monocyte-to-lymphocyte ratio (MLR) for post-ESD esophageal stricture of EEC. Material/Methods A retrospective study of 285 patients with EEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Prosthetic joint infection (PJI) is one of the most severe complications after TKA [32]. Several studies have shown that PJI after knee surgery is associated with higher NRL and PLR levels [33][34][35][36][37]. Golge et al [38] found the value of 2.45 to be a cut-off point for infection after TKA.…”
Section: Discussionmentioning
confidence: 99%
“…Prosthetic joint infection (PJI) is one of the most severe complications after TKA [32]. Several studies have shown that PJI after knee surgery is associated with higher NRL and PLR levels [33][34][35][36][37]. Golge et al [38] found the value of 2.45 to be a cut-off point for infection after TKA.…”
Section: Discussionmentioning
confidence: 99%